Why is the transference theory of causation insufficient? The challenge of the Aharonov-Bohm effect. (August 2018) - Ardourel, Vincent; Guay, Alexandre
Abstract: The transference theory reduces causation to the transmission (or regular manifestation) of physical conserved quantities, like energy or momenta. Although this theory aims at applying to all fields of physics, we claim that it fails to account for a quantum electrodynamic effect, viz. the Aharonov-Bohm effect. After having argued that the Aharonov-Bohm effect is a genuine counter-example for the transference theory, we offer a new physicalist approach of causation, ontic and modal, in which this effect is embedded. Highlights: Based on the Aharonov-Bohm effect, an argument against the transference theory of causation. The development of an interactionist theory of causation. The development of a modal version of the interactionist theory of causation in order to accommodate quantum phenomena.